Modellierung mehrkomponentiger Materialsysteme für die Phasenfeldmethode und Analyse der simulierten Mikrostrukturen - Kellner, Michael (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2021)
In this work, the solidification process of the high-temperature materials NiAl-34Cr und Nb-Si is investigated with the phase-field method. This work includes an entire investigation chain from the modeling of the material systems to the conduction of representative phase-field simulations, and finally to the analyzation of the resulting microstructures.